Stocks of Images. Issue 2 (1st June 2021) - Feuchtwang, Stephan
Abstract: What kind of knowledge is created through systems of divination? I will contend that the form of such knowledge is a type of pattern recognition—patterns that emerge in reference to a cosmology and by means of a stock of images. Divination creates knowledge of a moment and its circumstances. Reference to a sense of the encompassing world raises the issue of how any one means of divination and its outcomes is bound historically to a civilization. That will be my secondary topic of reflection. I will conclude with a discussion of worlds, recent history, speculation, and the ontology of divination in relation to the experience of uncertainty in which the object of knowledge is the momentary and its circumstances.